TANGGUNGJAWAB PEMBERI DAN PENERIMA PROTOKOL NOTARIS TERHADAP PROTOKOL NOTARIS YANG HILANG ATAU RUSAK - MUHAMMAD FAISAL NST (PREMISE LAW JURNAL, 2017)
Notary’s protocol is a part of the administration in a notary’s office which plays a very essential function and role so that the notary can perform his duty well and properly. It is a State’s archive that has to be organized and managed well. Therefore, it has to be treated like a State’s document which has to always be saved and conserved to remain authentic. It has to be kept and preserved in any condition even though the notary takes leave, retires, or passes away. However, despite the safe management, notary’s protocol may be damaged due to the paper age that only lasts about ten years, eaten by termites, missing because of natural disaster that strikes the area where notary’s office is located, or missing due to its holder’s negligence. Keywords: Liability, Notary’s Protocol, Missing, Damaged